On the Advanced Technique of Mathematical and Computer Simulation of Filtration Processes in Porous Media under the Influence of Physical and Chemical Factors - Gerus, Volodymyr (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The proposed improvement of the technique for deriving filtration equations in soils with variable porosity is described. The technique is based on the application of the apparatus of complete derivatives in the soil phase continuity equations. Examples of filtration equations in the case of a deformable and non-deformable skeleton of a porous medium are given.